Math, asked by niharika772713, 6 months ago


If 2cos a + sine a=1 then
7 cos a + 6sin a=?

Answers

Answered by aksharxeroxmlkp7iexu
0

Answer:

menu

myCBSEguide

person

If 2cos theta -sin theta =x …

Homework Help

CBSE

Class 10

Mathematics

If 2cos theta -sin theta =x and cos theta - 3sin theta =y,prove that 2xsquare +y square -2xy =5

Posted by Puneet Kothari 1 year, 7 months ago

CBSE > Class 10 > Mathematics

1 answers

Sia 1 year, 7 months ago

Given, 2 cosθ - sinθ =x and

cosθ - 3 sinθ =y

Put the values of x and y in 2x2+y2−2xy (LHS) , we get

= 2(2 cosθ − sinθ)2 + (cosθ − 3 sinθ)2 − 2(2 cosθ − sinθ)(cosθ − 3 sinθ)

= 2(4cos2 θ− 4cosθ sinθ + sin2θ) + (cos2 θ− 6cosθ sinθ + 9sin2 θ) − 2(2cos2 θ− 7cosθ sinθ + 3sin2 θ)

= 8cos2θ − 8cosθ sinθ + 2sin2θ + cos2θ − 6cosθ sinθ + 9sin2θ − 2(2cos2 θ− 7cosθ sinθ + 3sin2 θ)

= 8cos2θ − 8cosθ sinθ + 2sin2θ + cos2θ − 6cosθ sinθ + 9sin2θ − 4cos2θ + 14cosθ sinθ − 6sin2θ

= 5cos2θ + 5sin2θ

= 5(cos2θ + sin2θ)

=5

= RHS

Answered by satpalparjapat0
0

(2cosa)^2=(1-sina)^2

4cos^2a=1+sin^2a-2sina

4-4sin^2a=1+sin^2a-2sina

5sin^2a-2sina-3=0

5sin^2a-5sina+3sina-3=0

5sina(Sina-1)+3(sina-1)=0

(5sina+3)*(sina-1)=0

Sina=-3/5 or Sina=1

therefore for sina=-3/5 cosea=4/5

7cosa+6sina=7(-3)/5+6(3)/5=-3/5

for sina=1 and cosa=0

7cosa+6sina=6*1=6

Similar questions